2021
DOI: 10.3390/cancers13153792
|View full text |Cite
|
Sign up to set email alerts
|

Fluorescence Image-Guided Surgery for Thyroid Cancer: Utility for Preventing Hypoparathyroidism

Abstract: Background: Hypoparathyroidism is one of the most frequent complications of thyroid surgery, especially when associated with lymph node dissection in cases of thyroid cancer. Fluorescence-guided surgery is an emerging tool that appears to help reduce the rate of this complication. The present review aims to highlight the utility of fluorescence imaging in preserving parathyroid glands during thyroid cancer surgery. Methods: We performed a systematic review of the literature according to PRISMA guidelines to id… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 79 publications
0
22
0
Order By: Relevance
“…Small next-generation sequencing (NGS) studies with < 20 patients have reported actionable genetic alterations in approximately one half to two thirds of the cases [40]. Notably, NTRK1 was present in 5% and a high tumor mutational burden in approximately 20% [24,40].…”
Section: Molecular Insights Ongoing Investigations and Future Perspec...mentioning
confidence: 99%
See 1 more Smart Citation
“…Small next-generation sequencing (NGS) studies with < 20 patients have reported actionable genetic alterations in approximately one half to two thirds of the cases [40]. Notably, NTRK1 was present in 5% and a high tumor mutational burden in approximately 20% [24,40].…”
Section: Molecular Insights Ongoing Investigations and Future Perspec...mentioning
confidence: 99%
“…Small next-generation sequencing (NGS) studies with < 20 patients have reported actionable genetic alterations in approximately one half to two thirds of the cases [40]. Notably, NTRK1 was present in 5% and a high tumor mutational burden in approximately 20% [24,40]. The inclusion of standardized reporting systems, such as the AJCC 8th edition of the International Collaboration on Cancer Reporting (ICCR), is expected to yield useful data for establishing prognostic stages.…”
Section: Molecular Insights Ongoing Investigations and Future Perspec...mentioning
confidence: 99%
“…The recommended dose for PG visualization is 0.2-0.5 mg/kg, which may be repeated as required without exceeding the maximal daily dose of 5 mg/kg [56][57][58]. Both techniques have shown promising results in several studies in the literature [46][47][48]54,59,60].…”
Section: Identification Of Parathyroid Glands With Fluorescence Systemsmentioning
confidence: 99%
“…Over the years, the mainstays of parathyroid protection have been visual detection of PGs, capsular dissection technique, and autotransplantation of nonperfused glands ( 3 , 5 , 6 ). Recently, near-infrared fluorescence imaging (autofluorescence and indocyanine green angiography(ICGA)) has emerged as a novel intraoperative tool to help detect, identify, and preserve the PGs during thyroid surgery ( 7 ). Near-infrared autofluorescence is based on the endogenous fluorophore in PGs and facilitates the identification and preservation of PGs, thereby reducing the rate of postoperative hypoparathyroidism ( 7 ).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, near-infrared fluorescence imaging (autofluorescence and indocyanine green angiography(ICGA)) has emerged as a novel intraoperative tool to help detect, identify, and preserve the PGs during thyroid surgery ( 7 ). Near-infrared autofluorescence is based on the endogenous fluorophore in PGs and facilitates the identification and preservation of PGs, thereby reducing the rate of postoperative hypoparathyroidism ( 7 ). However, the adoption of autofluorescence has certain drawbacks ( 8 ): Thyroid tissue might present similar autofluorescence intensities with the parathyroid tissue in some cases; False positives signals may also occur from colloid nodules, brown fat, and metastatic lymph nodes; most importantly, autofluorescence is unable to assess the perfusion status and vitality of PGs.…”
Section: Introductionmentioning
confidence: 99%